Creative Teaching Model for Second Language Learning in the Post-Pandemic Era - Risna Rianti Sari; Alfiatus Syarofah; Harir Mubarok (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
Indonesia is currently trying to reorganize the education system post-pandemic by using hybrid learning system. In this hybrid learning process, lecturers are required to grow and develop their creativity. This article described the mapping of the model of second language teaching lecturers both English and Arabic at Maulana Malik Ibrahim State Islamic University of Malang on creativity in teaching, in particular to find out how well they understand the concept of creativity and the implementation of creative teaching in the form of classroom activities. This method used was qualitative approach with the type of content analysis. Data were collected through in-depth interviews with 21 second language lecturers, then the data were analyzed using Krippendorff content analysis. The results of this study indicated that second language lecturers had a comprehensive understanding of the demands of creativity in this post-pandemic, because they can clearly explained the meaning of creativity both in ideas and in its realization. In addition to understood creativity and its implementation in teaching activities, this research also showed the synergy between individual creativity as reflected in professional teaching and organizational creativity as seen from the readiness of this university to develop students' creative attitudes through support for campus facilities.